- 1-800-665-6601
- [email protected]

if: x → y ( read as, f maps X into Y).

The element of the set Y corresponding to the element x of X obtained by the rule f is denoted by f(x). Thus,

if the rule f determines y € Y when x € X then we shall have,

y = f(x)

Replacing x by (x + 2) in (1) we get,

f (x + 2 – 2) = 2 (x +2) + 5

f (x) = 2 x + 4 + 5

f (x) = 2 x + 9

Therefore f (x) = 2 x + 9

Substituting x = -1 in equation (1) we get,

F (-1) = 2 (-1)^2 + 3 (-1) +9

F (-1) = 2 * 1 – 3 + 9

F (-1) = 2 + 6 = 8

Therefore f(-1) = 8